Disciplinary administrative process in the public administration: (Revista Paradigma, 2020)
The present work has a reflected scope on the feasibility of the use of agreements in the administrative disciplinary process provided for in Law No. 8,112 / 90. The research uses the logical-deductive method, with bibliographical research on the subject, through legal articles , doctrinal, juridical magazines, jurisprudential, constitutional and infraconstitutional norms. The fundamental idea is the change of focus on the logic of the mechanisms of control, the cessation of thought as a strictly sanctioning strand, establishing it as a pacifying instrument, negotiating it as internal disputes, according to the precepts of the Constitution of the Republic of 1988 and the Code of Civil Procedure of 2015. It was envisaged that the cooperative process to the PAD, due to some benefits that favors.